2016
DOI: 10.1007/978-3-319-30133-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Framing or Gaming? Constructing a Study to Explore the Impact of Option Presentation on Consumers

Abstract: The manner in which choice is framed influences individuals' decision-making. This research examines the impact of different decision constructs on decision-making by focusing on the more problematic decision constructs: the un-selected and pre-selected optout. The study employs eye-tracking with cued retrospective think-aloud (RTA) to combine quantitative and qualitative data. Eye-tracking will determine how long a user focuses on a decision construct before taking action. Cued RTA where the user will be show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These strategies and techniques may involve various ways of wording, including an everyday style (eg, "heart attack") versus a technical style (eg, "myocardial infarction"), a tentative style (eg, "presumably similar") versus a nontentative style (eg, "similar"), a neutral style (eg, "methodological mistakes") versus an aggressive style (eg, "really dumb methodological mistakes"), an emotional style versus a nonemotional style, and an enthusiastic style versus a nonenthusiastic style. [36,[41][42][43][44]. They may also include the use of personal references (eg, first-person and second-person pronouns), personal testimonials, specific conversational frameworks or prompts, and other verbal means of communication [45][46][47].…”
Section: Language Use and Its Significance In Ca Communicationmentioning
confidence: 99%
“…These strategies and techniques may involve various ways of wording, including an everyday style (eg, "heart attack") versus a technical style (eg, "myocardial infarction"), a tentative style (eg, "presumably similar") versus a nontentative style (eg, "similar"), a neutral style (eg, "methodological mistakes") versus an aggressive style (eg, "really dumb methodological mistakes"), an emotional style versus a nonemotional style, and an enthusiastic style versus a nonenthusiastic style. [36,[41][42][43][44]. They may also include the use of personal references (eg, first-person and second-person pronouns), personal testimonials, specific conversational frameworks or prompts, and other verbal means of communication [45][46][47].…”
Section: Language Use and Its Significance In Ca Communicationmentioning
confidence: 99%
“…In recent years, more and more people use enthusiastic language to disseminate information and persuade their audiences in diverse contexts. For example, Ghose et al [27] observed that, instead of just writing positive comments on online marketplace platforms, “buyers tend to use superlatives and highly enthusiastic language to praise a good merchant.” In another study, Barry et al [28] pointed out that enthusiastic language is used as a persuasion tactic on commercial websites. Furthermore, enthusiastic language is nowadays often used to communicate scientific findings.…”
Section: Introductionmentioning
confidence: 99%